2021
DOI: 10.1016/j.eclinm.2021.100734
|View full text |Cite
|
Sign up to set email alerts
|

Antibody titers against SARS-CoV-2 decline, but do not disappear for several months

Abstract: Interpretation: Although the number of patients is limited, our results show that the antibody response against the first SARS-CoV-2 infection in symptomatic patients is typical of that observed in an acute viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
115
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 49 publications
29
115
2
Order By: Relevance
“…Our study showed significantly higher anti-N and anti-RBD/S1 levels when there was a more severe infection, a higher number of clinical symptoms, and fever. This association with disease severity has previously been reported (den Hartog et al, 2021;L'Huillier et al, 2021;Yamayoshi et al, 2021). However, we were not able to confirm the correlation between disease severity and the decrease in antibody levels over time reported by Yamayoshi et al (2021).…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Our study showed significantly higher anti-N and anti-RBD/S1 levels when there was a more severe infection, a higher number of clinical symptoms, and fever. This association with disease severity has previously been reported (den Hartog et al, 2021;L'Huillier et al, 2021;Yamayoshi et al, 2021). However, we were not able to confirm the correlation between disease severity and the decrease in antibody levels over time reported by Yamayoshi et al (2021).…”
Section: Discussioncontrasting
confidence: 78%
“…This association with disease severity has previously been reported (den Hartog et al, 2021;L'Huillier et al, 2021;Yamayoshi et al, 2021). However, we were not able to confirm the correlation between disease severity and the decrease in antibody levels over time reported by Yamayoshi et al (2021). Instead, our data indicate stable antibody levels and long-lasting immunity, irrespective of the disease severity.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Several studies have demonstrated decreasing antibody levels in COVID-19 patients over time, leading to concerns for waning immunity. [45][46][47] However, for a more comprehensive picture of the longevity of immunity, memory B cell and T cell responses should be studied in parallel, as these cells would be important players in providing protection upon re-exposure to SARS-CoV-2. Here, we followed 17 patients for 5 months and 13 of those patients for 9 months after symptom onset, in order to assess antibody dynamics over time.…”
Section: Discussionmentioning
confidence: 99%
“…Longevity of immunological memory following SARS‐CoV‐2 infection is a question of particular relevance for informing public health policies and predicting the future course of the pandemic. Several studies have demonstrated decreasing antibody levels in COVID‐19 patients over time, leading to concerns for waning immunity 45–47 . However, for a more comprehensive picture of the longevity of immunity, memory B cell and T cell responses should be studied in parallel, as these cells would be important players in providing protection upon re‐exposure to SARS‐CoV‐2.…”
Section: Discussionmentioning
confidence: 99%